Classes (IntechOpen, 2021)
Stormy times are looming just around the corner during the next ten years. People all around the world are increasingly feeling that a major shake-up of our living conditions is in the air. The three most visible global dangers are an environmental collapse, a third world war, and an accelerating inequality of welfare between different parts of the human population. It is evident that these threatening developments are highly interdependent symptoms of the same social process: the dynamics of global political economy. We are in acute need of a theory that explores our options for a surviving human species. The major social entities involved in this change have to be identified: Classes.